Comparison of Routine Hematology, Coagulation, and Clinical Chemistry Parameters of Cynomolgus Macaques of Mauritius Origin With Cynomolgus Macaques of Cambodia, China, and Vietnam Origin. (July 2022) - Arndt, Tara; Meindel, Mandy; Clarke, Joseph; Shaw, Amanda; Gregori, Michela
Cynomolgus macaques ( Macaca fascicularis ) are commonly used in safety assessment and as translational models for drug development. Recent supply chain pressures, exportation bans, and increased demand for drug safety assessment studies exacerbated by the COVID-19 pandemic have prompted the investigation of utilizing macaques of different geographic origin in preclinical toxicity studies. This study compares routine hematology, coagulation, and clinical chemistry endpoints of 3 distinct subpopulations of mainland Asia origin (Cambodia, China, and Vietnam) with Mauritius origin macaques compiling results of 3, 225 animals from 123 regulatory toxicology studies conducted at North American and European Union contract research organization facilities between 2016 and 2019. Results were generally similar amongst the subpopulations compared in this study. Few notable differences in hematology test results and several minor differences in serum biochemistry and coagulation test results were identified when 3 distinct subpopulations of mainland Asia origin macaques were compared with Mauritius origin macaques. Our findings support the use of different origin macaques in drug development programs; however, emphasizes the importance of maintaining consistency in geographic origin of animals within a study.